What is nature capable of? Evidence, ontology and speculative medical humanities. Issue 3 (24th May 2016) - Savransky, Martin; Rosengarten, Marsha
Abstract : Expanding on the recent call for a 'critical medical humanities' to intervene in questions of the ontology of health, this article develops a what we call a 'speculative' orientation to such interventions in relation to some of the ontological commitments on which contemporary biomedical cultures rest. We argue that crucial to this task is an approach to ontology that treats it not as a question of first principles, but as a matter of the consequences of the images of nature that contemporary biomedical research practices espouse when they make claims to evidence, as well as the possible consequences of imagining different worlds in which health and disease processes partake. By attending to the implicit ontological assumptions involved in the method par excellence of biomedical research, namely the randomised controlled trial (RCT), we argue that the mechanistic ontology that tacitly informs evidence-based biomedical research simultaneously authorises a series of problematic consequences for understanding and intervening practically in the concrete realities of health. As a response, we develop an alternative ontological proposition that regards processes of health and disease as always situated achievements. We show that, without disqualifying RCT-based evidence, such a situated ontology enables one to resist the reduction of the realities of health and disease to biomedicine's current forms of explanation. In so doing, we call for medical humanities scholars to actively engage in the speculative question of what nature may be capable of.